Social and Emotional Wellbeing Screening for Aboriginal and Torres Strait Islanders within Primary Health Care: A Series of Missed Opportunities? - Langham, Erika; McCalman, Janya; Matthews, Veronica; Bainbridge, Roxanne Gwendalyn; Nattabi, Barbara; Kinchin, Irina; Bailie, Ross (Frontiers in Public Health, 2017)
Background: Social and emotional wellbeing (SEWB) is a critical determinant of health outcomes for Indigenous Australians. The present study examined the extent to which primary healthcare services (PHS) undertake SEWB screening and management of Aboriginal and Torres Strait Islander clients, and the variation in SEWB screening and management across Indigenous PHS. Methods: Cross-sectional analysis between 2012–2014 of 3407 Indigenous client records from a non-representative sample of 100 PHSs in four Australian states/territory was undertaken to examine variation in the documentation of: 1) SEWB screening using identified measurement instruments, 2) concern regarding SEWB, 3) actions in response to concern, and 4) follow up actions. Binary logistic regression was used to determine the factors associated with screening. Results: The largest variation in SEWB screening occurred at the state/territory level. The mean rate of screening across the sample was 26.6%., ranging from 13.7% to 37.1%. Variation was also related to PHS characteristics. A mean prevalence of identified SEWB concern was 13% across the sample, ranging from 9% to 45.1%. For the clients where SEWB concern was noted, 25.4% had no referral or PHS action recorded. Subsequent internal PHS follow up after one month occurred in 54.7% of cases; and six-monthly follow up of referrals to external services occurred in 50.9% of cases. Conclusion: Our findings suggest that the lack of a clear model or set of guidelines on best practice for screening for social and emotional wellbeing in Indigenous health may contribute to the wide variation in SEWB service provision. The results tell a story of missed opportunities: 73.4% of clients were not screened and no further action was taken for 25.4% for whom a SEWB concern was identified. There was no follow up for just under half of those for whom action was taken. There is a need for the development of national best practice guidelines for SEWB screening and management, accompanied by dedicated SEWB funding and training for health service providers as well as ongoing monitoring of adherence with the guidelines. Further research on barriers to screening and follow up actions is also warranted.